Hydrogen Sulfide Facilitates the Impaired Sensitivity of Carotid Sinus Baroreflex in Rats with Vascular Calcification - Li, Hui; Teng, Xu; Yang, Rui; Guo, Qi; Xue, Hongmei; Xiao, Lin; Duan, Xiaocui; Tian, Danyang; Feng, Xiaohong; Wu, Yuming (Frontiers in Pharmacology, 2017)
Arterial baroreflex is a general mechanism maintaining cardiovascular homeostasis; its sensitivity is reduced in vascular calcification (VC). Hydrogen sulfide (H2S) treatment facilitates baroreflexive sensitivity in normal and hypertensive rats. Here, we aimed to detect the effect of H2S on baroreflexive sensitivity in rats with VC. The rat VC model was induced by vitamin D3 plus nicotine for 4 weeks. The sensitivity of baroreflex was detected by perfusing the isolated carotid sinus. VC was assessed by hematoxylin and eosin (H&E) staining, Ca2+ content and alkaline phosphatase (ALP) activity. Protein levels were detected by western blot analysis. Vitamin D3 plus nicotine induced structural disorder and elevated Ca2+ content in the aortic and carotid arterial wall and increased plasma ALP activity. In the calcified aorta and carotid artery, protein levels of contractile phenotype markers of vascular smooth muscle cells (VSMCs) were downregulated and that of osteoblast-like phenotype markers and endoplasmic reticulum stress (ERS) markers were upregulated. NaHS treatment ameliorated the histologic disorder and Ca2+ content in the calcified aorta and carotid artery, inhibited the elevated plasma ALP activity, and prevented the transformation of the VSMC phenotype and activation of ERS in rats with VC. Chronic NaHS treatment blunted the sensitivity of the carotid sinus baroreflex and acute NaHS treatment dose-dependently improved the sensitivity in rats with VC. Our results suggested that H2S could directly facilitate the impaired sensitivity of baroreflex in rats with VC and ameliorate VC, which might provide new target and strategy for regulation of the baroreflex and therapy of VC.